World Map and Flashcard Media for Country Identification: Peta Dunia dan Kartu Flash untuk Identifikasi Negara - Risa Dwi Novita; Yuli Astutik (Academia Open, 2025)
General Background: Visual learning media play a significant role in creating meaningful and engaging classroom experiences, particularly in geography and language education. Specific Background: The integration of a world map and flashcards is designed to support senior high school students in identifying countries and describing their characteristics through interactive and collaborative activities. Knowledge Gap: Previous discussions on instructional media often focus on digital tools, while the structured combination of a three-dimensional world map and bilingual flashcards remains underexplored in classroom practice. Aims: This article aims to present the design and classroom implementation of world map–based learning media for country identification. Results: The implementation demonstrates that students actively participate in group discussions, analyze descriptive information, and identify countries based on geographical location and characteristic features. Novelty: The media combines a raised-surface world map with bilingual descriptive flashcards to create a structured, collaborative, and explorative learning experience. Implications: This learning media provides an alternative instructional strategy for geography and English teachers to facilitate spatial understanding, descriptive skills, and active classroom engagement. Keywords: World Map Media, Flashcard Learning, Country Identification, Visual Learning, Geography Education Key Findings Highlights: Students engaged in structured group discussions using spatial and descriptive cues. The media design integrates three-dimensional mapping with bilingual descriptive cards. Classroom activities promoted observation, analysis, and collaborative exploration.